Factors Persuading Tourists to Visit SWAT Valley, Pakistan - Nasir Ali; Bushra Khan; Syeda Kiran Zehra; Aftab Hussain Tabasam; Nowsherwan Sarwar; Syed Tehseen Jawaid (Journal of Management Practices, Humanities and Social Sciences, 2023)
The study identified the factors that persuade tourists (local or international) to visit SWAT, Khyber Pakhtunkhwa, Pakistan and whether these factors successfully created positive behavioural intentions among visitors. In total, 684 responses from local and international tourists were collected through a questionnaire survey. The responses were analysed by employing the PLS-SEM technique on SMARTPLS software. Results revealed that most tourists are satisfied with the destination brand, attraction, hospitality, and entertainment given by SWAT's people & local government. These factors create positive future behaviour (i.e., intention to recommend and intention to revisit) among visitors, except transportation which is the only element that failed to attract tourists due to inadequate mechanisms in SWAT. This study highlighted that Pakistan Tourism Development Corporation (PTDC), being a responsible authority in Pakistan for tourism-related matters, still needs to improve and develop tourist destinations in Pakistan to sustain tourism. This study is a pioneer attempt to identify the factors that persuade tourists (local or international) to visit SWAT, Khyber Pakhtunkhwa, Pakistan, using a Likert scale survey questionnaire.